Strategic Management of Digital-Based Learning in Enhancing Religious Literacy and Critical-Contextual Understanding of Islamic Teachings in Madrasah - Sukawati Sukawati; Ahmad Syarifuddin Zuhri; M. Makhrus Ali; Meilisa Sajdah (Universitas Nurul Jadid, 2025)
The integration of digital technology into Islamic education has created new opportunities for enhancing students’ religious literacy while simultaneously presenting challenges related to the management of learning processes. This study examines how digital-based learning is strategically managed in a madrasah located in North Lampung, Indonesia, with a particular focus on its role in fostering critical and contextual understanding of Islamic teachings. Employing a qualitative case study design, the research explores institutional planning, classroom implementation, and evaluative practices as interconnected processes shaping digital learning. The findings reveal that digital learning is most effective when supported by structured management, where leadership plays a central role in aligning technological use with educational objectives. In classroom practices, digital media facilitates more interactive and participatory learning, enabling students to engage with religious content beyond rote memorization. Furthermore, evaluative practices emphasize students’ ability to interpret, relate, and critically respond to Islamic teachings in contemporary contexts. The study highlights that digital learning, when systematically managed, contributes not only to improved access to knowledge but also to the development of deeper and more reflective understanding. These findings underscore the importance of integrating managerial strategies with pedagogical practices to ensure the sustainability and effectiveness of digital learning in Islamic educational institutions.